Efektifitas Peran Konselor Sebaya dalam Meningkatkan Resiliensi Remaja yang Ditinggal Mati Orang Tuanya Akibat Korban Covid-19 di Jombang - Hasanah, Uswatun (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Covid-19 pandemic has had a very heavy impact on society, especially for teenagers who have lost one or both parents who have become victims of the violence of Covid-19. They feel quite heavy psychological impacts such as stress, depression and a feeling of helplessness and this causes a weakening of their fighting power adolescents in problems solving. This study aims to examine the effectiveness role of peer counselors in increasing the resilience of adolescents whose parents have died as a result of Covid-19 victims in Jombang. This research is a quasi-experimental study using the One Group Pretest Posttest Design model, where pretest measurements are carried out before the subjects are given treatment in the form of peer counseling and after being given treatment, resilience measurements are carried out again in adolescents who are the research subjects. The sampling technique uses purposive sampling, the number of subjects is 100 adolescents aged 14-18 years with SMP and SMA education levels. The research findings show that the role of peer counselors is very effective in increasing resilience in adolescents whose parents have died as a result of being victims of Covid-19. There was an increase in the adolescent resilience of mean score 24.450, and the results of the paired t-test obtained t = -53.852; df = 99 with a significance of 0.000 (p <0.01) its means that there is a very significant difference in the resilience abilities of adolescents between before receiving peer counseling and after receiving peer counseling.